Self-mineralizing Ca-enriched Methacrylated Gellan Gum Beads for Bone Tissue Engineering - Vieira, S. (2019)
In this study, methacrylated gellan-gum (GG-MA) heteropolysaccharide is proposed as a hydrogel for drug delivery and bone tissue engineering applications. Calcium-enriched beads obtained from the crosslinking of 1% (w/v) GG-MA solutions with 0.1Â MÂ CaCl2 were investigated, considering their intrinsic capacity to promote self-mineralization by ion binding and deposition. Indeed, when immersed in a physiological environment, the Ca-enriched beads promoted the development of a bone-like apatite layer, as confirmed by EDS and XRD chemical analysis. Additionally, the mild production process is compatible with drugs incorporation and release. After encapsulation, Dextran with different molecular weights as well as Dexamethasone 21-phosphate were efficiently released to the surrounding environment. The engineered system was also evaluated considering its biocompatibility, by means of qualitative determination of total complement activation, macrophage proliferation, cytokine release and in vitro cell culture. These experiments showed that the developed hydrogels may not stimulate a disproportionate pro-inflammatory reaction once transplanted. At last, when implanted subcutaneously in CD1 male mice up to 8 weeks, the beads were completely calcified, and no inflammatory reaction was observed. Summing up, these results show that calcium-enriched GG-MA hydrogel beads hold great potential as news tools for bone tissue regeneration and local drug delivery applications.